Pengaruh Metode Storytelling Terhadap Kepatuhan Anak Dalam Menjaga Kebersihan Gigi - Warda M; Rony Alexander Latumenasse; Imelda Appulembang; Nurlaelah Nurlaelah; Rischa Hamdanesti; Nurnainah Nurnainah (Barongko: Jurnal Ilmu Kesehatan, 2026)
Children's adherence to dental hygiene is a crucial factor in preventing dental and oral diseases, particularly caries, which is common among school-aged children. This low adherence is often caused by a lack of understanding and motivation regarding the importance of maintaining good dental hygiene. The storytelling method is believed to be an effective educational strategy because it aligns with the developmental characteristics of children who enjoy stories and imagination. This study aimed to determine the effect of the storytelling method on children's adherence to dental hygiene. The study used a quasi-experimental design with a pre-test and post-test control group design. The sample consisted of 40 children aged 6–8 years, divided into two groups: an experimental group educated using the storytelling method, and a control group educated using the conventional lecture method. Data were collected through a toothbrushing adherence questionnaire covering brushing frequency, time, and technique. The analysis showed a significant increase in children's adherence scores in the experimental group after treatment (p = 0.001), while the increase was not significant in the control group (p = 0.213). An independent t-test showed a significant difference between the two groups after the intervention (p = 0.004). In conclusion, the storytelling method has a significant impact on increasing children's adherence to dental hygiene. This approach can be implemented by teachers, healthcare workers, and parents as a fun and effective educational method to foster clean and healthy living habits from an early age.